Review Paper on Various Methodology of Text Extraction from Image - Patil, Rucha; Khati, Smruti; Thakur, Tulsi; Katragadda, Harshita; Ambulkar, Neha; Bhakare, Ketki (Journal of Advance Research in Computer Science & Engineering (ISSN 2456-3552), 2015)
This review presents the various text extraction techniques and also compares the research results of various researchers in the domain of text extraction. A generic character recognition system has different stages like noise removal, skew detection and correction, segmentation, feature extraction and character recognition. Input is digitized image containing any text, which is preprocessed to segment it into normalized individual word and letters. The OCR, Neural Network, SVM are the various methods for text extraction. Text extraction helps to preserve history by making information efficiently searchable, easily manageable without the need for human labor.